Analysis of the Influence of Germas Implementation on the Health of the Elderly in the Working Area of the Brohol Tebing Tinggi Health Center - Asrinab, Asrinab; Effendy, Ismail; Nasution, Ramadhani Syafitri (Universitas Ibn Khaldun Bogor, 2025)
The low implementation of germas has a great impact on public health, namely the increase in the number of diseases in the elderly. This study aims to analyze the effect of the implementation of Germas on the health of the elderly in the working area of the Berohol Tebing Tinggi Health Center.This study uses a type of quantitative research analytical survey with a cross sectional study design. The location of this research was carried out in the working area of the Berohol Tebing Tinggi Health Center. The research population is all elderly people who visit and actively participate in the Germas activity program in the work area of the Berohol Tebing Tinggi health center as many as 216 people. The number of samples in this study is 68 people. The technique used is purposive sampling. The survey data was analyzed using the chi-square test and logistics regression. The results of the study showed that there was an influence of physical activity on the health of the elderly, there was an influence of fruit and vegetable consumption culture on the health of the elderly who followed the implementation of Germas in the work area of the Berohol Health Center, there was an effect of smoking on the health of the elderly, there was an effect of not consuming alcoholic beverages on the health of the elderly, there was an effect of conducting periodic health checks on the health of the elderly, there was an effect of maintaining environmental cleanliness on the health of the elderly. health of the elderly who follow the implementation of Germas in the work area of the Brohol Tebing Tinggi Health Center, there is an influence of using latrines on the health of the elderly. The variable that most affects the health of the elderly who follow the implementation of Germas in the work area of the Brohol Tebing Tinggi health center is the variable of conducting periodic health checks. Based on the results of the research, it is suggested that the health center be more aggressive in promoting Germas activities and improving health services specifically for the elderly as well as providing input and improvement of the Germas program.